Effect of Perineal Massage on the Rate of Episiotomy - Farideh Akhlaghi; Zeynab Sabeti Baygi; Mohsen Miri; Mona Najaf Najafi (Tehran University of Medical Sciences, 2019)
Objective: Women frequently experience perineal damage after a vaginal delivery. This study aimed to investigate the effect of perineal massage (PM) during labor on the need for episiotomies. Materials and methods: The study is a double-blind randomized clinical trial conducted with 99 patients (n=49 controls; n=50 cases). Participants comprised of nulliparous pregnant women aged from 18 to 35 years in the 37th-42nd week of gestation, who referred to the Um-al-Banin Hospital of Mashhad from July to October 2018, for vaginal delivery and were in the active stage of labor. Allocation to study groups was based on a random allocation list generated by a software application. PM was performed for the cases in the active stage four times, each lasting for two minutes at intervals of half an hour. The massage was continued at the beginning of the second stage of labor for ten minutes. Control women received routine care. The delivery was practiced by a midwife who was blinded to the study groups and the performance or non-performance of massage. Data were analyzed in SPSS software version 16. Results: The need for episiotomy was significantly lower in the PM group than in the control group (p = 0.05). Spontaneous perineal tears were significantly higher in mothers of the PM group (p = 0.05. The spontaneous tear degree in the 20 mothers who did not require episiotomy (p = 0.5) and the degree of perineal tear in mothers who needed an episiotomy (n = 79; p = 0.1) were not significantly different in the two groups. In the PM group members who did not require episiotomy (n = 14) and the mother underwent a spontaneous tear, first-degree tears were more frequent than second-degree ones. The median duration of the active stage of labor until the stage completion was lower in the PM group than in the control group, although the difference did not reach statistical significance (p = 0.3). The median of the second stage duration in the control and intervention groups were 55 and 45 minutes, respectively, where the difference was significant (p = 0.002), and the median time of completion of the active stage until delivery in the PM group had reduced. Conclusion: PM had a significant impact on the reduction of the need for episiotomies and the duration of the second stage of labor. Thus, it can be suggested as a safe, simple, low-cost, and effective technique to reduce the perineal damage during delivery.